Three-dimensional simulation/printing-assisted surgery for symptomatic metastatic epidural spinal cord compression of posterior column: efficacy assessment based on 2-year follow-up - Sun, Zhicheng; Jia, Runze; Wang, Xiyang; Pang, Xiaoyang (Frontiers in Surgery, 2023)
Background: Surgical intervention is necessary for resolving the symptoms of the spinal cord and nerve compression caused by symptomatic metastatic epidural spinal cord compression. However, surgeons are constantly seeking ways to improve surgical efficiency and safety. This study aims to evaluate the efficacy of 3D simulation/printing-assisted surgery for symptomatic metastatic epidural spinal cord compression of the posterior column. Methods: We retrospectively analyzed the clinical data of patients who underwent surgical treatment for symptomatic metastatic epidural spinal cord compression of the posterior column in our hospital from January 2015 to January 2020. The simulated group underwent a 3D digital simulation of the lesion area using imaging data before surgery. Twelve patients in the simulated group also received 3D printing, while the direct surgery group did not receive any 3D simulation or printing. All patients were followed up for at least 2 years. We collected clinical data, including operation time, intraoperative blood loss, pedicle screw adjustment rate, intraoperative fluoroscopy times, the incidence of dural injury and cerebrospinal fluid leakage, VAS score, postoperative neurological function improvement, and tumor recurrence. Statistical analysis was performed using SPSS23.0, and P<0.05 was considered statistically significant. Results: A total of 46 patients were included in this study, with 20 in the simulated group and 26 in the non-simulated group. The simulated group had better operation time, intraoperative blood loss, screw adjustment rate, fluoroscopy times, and incidence of dural injury / cerebrospinal fluid leakage compared to the non-simulated group. The VAS scores of the two groups improved significantly after the operation and at the last follow-up compared to before the operation. However, there was no statistically significant difference between the two groups. There was also no statistically significant difference in neurological function improvement between the two groups. In the simulated group, 25% of patients relapsed, while in the non-simulated group, 34.61% of patients relapsed. However, there was no statistical difference between the two groups. Conclusion: Preoperative 3D simulation / printing-assisted surgery is a practical and feasible approach for treating symptomatic metastatic epidural spinal cord compression of the posterior column.